HUBUNGAN USIA, JENIS KELAMIN DAN TINGKAT KONSUMSI ZAT GIZI DENGAN TINGKAT KEMATANGAN KATARAK SENILIS - Ahmad Yani, Didik Wahyudi, SKM (STIKES Widya Husada Semarang, 2010)
The number of blindness height in Indonesia reach 1.47% representing highest number in south-east Asi regional, the main cause is cataract, one of the cataract type is senilis cataract which divided in four level that is insipien, imatur, matur, hipermatur. Target of the research type is sactional cross, population is cataract patient 517 taken by sample counted 89 people by simple sample random, matching with inklusi criterion. Data analysis wear Chi Square Test (X2) and continued with contingensi coefficient with trust storey level 95%. Result of research show highest percentage of senilis cataract patient is old age (65%), type of women (61gender%) storey, level consume deficit energi (29%) storey, level consume proyein (46%) storey, level consume deficit C vitamin ang less (36%) at matur cataract maturity storey level (55%). There are corelation with senilis cataract maturity storey level (p = 0,018, c = 0,018) there is gender relation with senilis cataract maturity storey level ( p = 0.021, c = 0,282). There is storey level relation consume energi with senilis cataract maturity storey level (p = 0.038, c = 0.361). There is relation consume protein with senilis cataract maturity storey level (p = 0.029, c = 0,370). There no corelation storey level consume C vitamin with senilis cataract maturity storey level (p = 0.025, c = 0,284). Suggested for the spreader of information to society specially old age concerning energi consumption, protein, related to senilis cataract maturity storey level Keyworrd : Age, Gender, Story Level Consume Energi, protein, C Vitamin, cataractSenilis yle=mso-bidi-font-weight:normal>Keywords : Behavior live healthy, women sex worker, prevention of IMS-HIV/AIDS.